2017
DOI: 10.3892/ijo.2017.4105
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic inhibitory effects on hepatocellular carcinoma with recombinant human adenovirus Aspp2 and oxaliplatin via p53-independent pathway in vitro and in vivo

Abstract: The present study was designed to investigate the synergistic inhibitory effects on hepatocellular carcinoma with recombinant human adenovirus Aspp2 (Aspp2-ad) and oxaliplatin via p53-independent pathway in vitro and in vivo. After being treated with Aspp2-ad and/or oxaliplatin for 24-48 h, HepG2P53-/- and Hep3B cells showed a significant growth inhibition compared with vehicle control. Combination group showed a synergetic effect, the inhibitory rates were all above 80% at 48 h point in HepG2P53-/- and Hep3B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…The combination of oxaliplatin plus GW4064 inhibits STAT3 signaling by restoring SHP expression Small heterodimer partner (SHP), a well-known target gene of FXR, inhibits tumorigenesis by repressing STAT3 activity (35). Various lines of evidence have established that oxaliplatin could decrease the expression of STAT3 to inhibit the progression of cancer (36,37). As expected, GW4064 treatment alone increased the protein level of SHP.…”
Section: Gsdme-dependent Pyroptosis Is Downstream Of the Bax-mitochonmentioning
confidence: 58%
“…The combination of oxaliplatin plus GW4064 inhibits STAT3 signaling by restoring SHP expression Small heterodimer partner (SHP), a well-known target gene of FXR, inhibits tumorigenesis by repressing STAT3 activity (35). Various lines of evidence have established that oxaliplatin could decrease the expression of STAT3 to inhibit the progression of cancer (36,37). As expected, GW4064 treatment alone increased the protein level of SHP.…”
Section: Gsdme-dependent Pyroptosis Is Downstream Of the Bax-mitochonmentioning
confidence: 58%
“…Furthermore, an increasing amount of research has reported that oncolytic adenoviruses are capable of infecting and expressing exogenous functional genes with no target cells. The functional/effector genes can be classified in four categories by their functions: (1) Tumor-suppressor gene (51, 52); (2) Cytotoxic gene; (3) Immune-modulating gene (53); (4) Tumor-antigens (54). The following is the detailed introduction of genes carried by oncolytic adenoviral vectors for HCC treatment.…”
Section: Genetic Modifications Of Oncolytic Adenovirusmentioning
confidence: 99%
“…p53 is determined as a novel tumor-associated gene which mutations or deletions are related to most of the cancer formation. Since the frequency of p53 gene mutation/deletion is as high as 50.0% (average, 30.0%) in HCC (51), converting abnormal conformations of mutant p53 to normal p53 or enhancing the apoptosis of tumor cells by providing the exogenous p53 gene and the associated genes becomes a promising therapeutic strategy. The recombinant human wild-type p53-carrying adenovirus (Gendicine) is a pioneer gene therapy product approved for clinical use in China (66, 67).…”
Section: Genetic Modifications Of Oncolytic Adenovirusmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential cytotoxic effect of napabucasin on HCC cells was evaluated in terms of the proliferation ability of multiple human and murine HCC cell lines, and compared to that of oxaliplatin and the plant-derived STAT3 inhibitor cryptotanshinone (Liu et al, 2017;Qin et al, 2017;Ji et al, 2019;Zhu et al, 2019). As shown in Figure 1, all drugs significantly decreased the viability of HCC cells in a concentration-dependent manner.…”
Section: Napabucasin Inhibits Hcc Cell Growth In Vitromentioning
confidence: 99%